Clinical and laboratory variables associated with mortality outcome in the post-operative pediatric cardiac surgery - Aline Cerqueira Santos Santana da Silva; Marluci Andrade Conceição Stipp; Fernanda Maria Vieira Pereira; Graciele Oroski Paes; Virginia Maria de Azevedo Oliveira Knupp (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To identify clinical and laboratory variables associated with mortality outcome in the post-operative pediatric cardiac surgery. Method: Descriptive, retrospective study carried out in three reference centers in Rio de Janeiro State, Brazil, from the collection in 120 medical reports of children with Congenital Heart Disease undergoing surgery. Data were analyzed by using central tendency measures and association tests between variables and mortality. p < 0.05 was considered. Results: We observed the mortality outcome in 10 (7.2%) of the children after analyzing all medical records. The dialysis and extracorporeal circulation times, aortic and surgical clamping variables were associated with mortality outcome (p < 0.05). Conclusion and Implications for practice: The identification of these variables is a major factor for the control of the main post-operative complications, allowing the recognition of subtle clinical alterations requiring attention and immediate intervention with consequent reduction of mortality.